Curative Stem Cell Transplantation for Severe Hb H Disease Manifesting From Early Infancy: Phenotypic and Genotypic Analyses. (2nd January 2016) - Surapolchai, Pacharapan; Sirachainan, Nongnuch; So, Chi-Chiu; Hongeng, Suradej; Pakakasama, Samart; Anurathapan, Usanarat; Chuansumrit, Ampaiwan
Abstract: Most people with Hb H disease live normal lives; however, a minority of cases requires lifelong regular transfusions. An atypical form of nondeletional Hb H disease was reported in a Thai boy, characterized by severe persistent hemolytic anemia since the age of 2 months. Molecular diagnosis revealed the apparent compound heterozygosity for the Southeast Asian (− − SEA ) and α2 polyadenylation (polyA) signal (AATA AA >AATA− −) deletions. The proband was successfully treated with allogeneic hematopoietic stem cell transplantation (HSCT). Accurate phenotypic and genotypic diagnosis in atypically severe Hb H disease is helpful for the understanding of its pathophysiology, the institution of appropriate management, and provision of genetic counseling and prenatal diagnosis. Hematopoietic stem cell transplantation is a potentially curative treatment option for this severe α-thalassemia (α-thal) syndrome.